2003
DOI: 10.1099/mic.0.25959-0
|View full text |Cite
|
Sign up to set email alerts
|

Two new cellulosome components encoded downstream of celI in the genome of Clostridium thermocellum: the non-processive endoglucanase CelN and the possibly structural protein CseP

Abstract: Clostridium thermocellum produces a great number of extracellular cellulases which are free or cellulosome-bound. The nucleotide sequence of a gene cluster containing the genes celI, celN and cseP was determined from C. thermocellum strain F7. Gene products Cel9I and Cel9N are structurally related enzymes having a glycosyl hydrolase family 9 and a carbohydrate-binding module (CBM3c), but show characteristic differences: Cel9I is a non-cellulosomal protein with an additional CBM (CBM3b), whereas Cel9N contains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 36 publications
6
55
1
1
Order By: Relevance
“…The first two operons found are in the cipA cluster as two tandem operons, including cipA plus olpB and orfp2 plus olpA ("Attachment of cellulosomes to the cell surface" above). More recently, a noncellulosomal endoglucanase, CelI, was shown to be clustered with cellulosomal cellulase CelN and a possible cellulosomal structural, component CseP (for cellulosomal element protein) (373). cseP codes for a type I dockerin-containing protein and is in the opposite strand and likely transcribed independently from celI and celN.…”
Section: Cellulase Gene Clustersmentioning
confidence: 99%
See 2 more Smart Citations
“…The first two operons found are in the cipA cluster as two tandem operons, including cipA plus olpB and orfp2 plus olpA ("Attachment of cellulosomes to the cell surface" above). More recently, a noncellulosomal endoglucanase, CelI, was shown to be clustered with cellulosomal cellulase CelN and a possible cellulosomal structural, component CseP (for cellulosomal element protein) (373). cseP codes for a type I dockerin-containing protein and is in the opposite strand and likely transcribed independently from celI and celN.…”
Section: Cellulase Gene Clustersmentioning
confidence: 99%
“…CelF, the CelS equivalent in C. cellulolyticum, also displays significant activity in reducing the viscosity of a CMC solution (271). Some of the cloned endoglucanase genes are celA (26), celB (105), celC (298), celD (143,326), celE (113), celF (245), celG (188), celH (361), celI (101,123,373), celJ (encoding component S2 of the complex) (1,8), celM (162), celN (373), celQ (9), celT (172), and celX (113).…”
Section: Genes and Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymeric and oligomeric substrates were hydrolysed to completion under the conditions stated above. Hydrolysis products were separated on silica gel 60 plates, as described previously (Zverlov et al, 2003) or by HPLC (Beckmann System Gold, equipped with a deashing and a HPX-42A column, Bio-Rad) and refractometric sugar detection (ERC-7512, Erma).…”
Section: Denaturing Gel Electrophoresis (Sds-page) and Zymogrammentioning
confidence: 99%
“…The extreme stabilities (e.g., pH and thermal) and multifunctional nature of enzymes produced by these cellulosome-expressing bacteria have revolved the attention of scientist on to understanding the structure and function of their genetic makeup in order to mimic the innate abilities. On account of the obvious benefits reported in the literature, scientists have consistently investigated the gene (Yagüe et al 1990;Zverlov et al 2003;Koeck et al 2013), fusion/modification of enzymes (Ciolacu et al 2010;Lee et al 2010;Ye et al 2010;Lee et al 2011;Nakashima et al 2014), and the optimal growth (Islam et al 2013;Reed et al 2014) of these useful microbes to harness their inherent benefits. For example, the biochemical and biophysical characteristics of multimodular enzymes from Clostridium thermocellum (Zverlov et al 2005;Tachaapaikoon et al 2012;Brunecky et al 2012;Hirano et al 2013;Yuan et al 2015) and Thermotoga maritima (Chhabra et al 2002;Carvalho et al 2004;Pereira et al 2010;Wu et al 2011) have been reported.…”
Section: Bacteria Sourcesmentioning
confidence: 99%